Impact of Starter Fertilizer on Cotton Growth, Development, Lint Yield, and Fiber Quality Production for an Early Planted No‐Till System. Issue 1 (1st December 2013) - Pettigrew, William T.; Molin, William T.
Abstract : Improved yield potentials occur when planting cotton ( Gossypium hirsutum L.) early, but cool conditions associated with early planting can hamper seedling growth. Starter fertilizers could be a source of P for seedling growth under cool conditions due to reduced soil P mineralization. The objective was to document how cotton cultivars responded to starter fertilizer application when planted early in a no‐till production system. Seven cultivars were grown no‐till during 2008 through 2010. Plots received an in‐furrow starter fertilizer application or were untreated. Dry matter partitioning, light interception, lint yield, and fiber quality data were collected. Stands were reduced 20% by the starter fertilizer. Few growth differences were detected by treated and untreated plots although the starter fertilizer did elicit a single 17% increase in the blooming rate at 90 days after planting in 2009. Despite the lack of growth differences and the reduced stands, starter fertilizer increased yields 4% in 2 of the 3 yr. Few consistent fiber quality differences were detected between the fertility treatments. Starter fertilizer application can produce a modest yield improvement when used in an early planting no‐till cotton production system. Producers must decide whether this modest yield boost is economically sufficient to justify the additional input costs.